English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

please help me figure out this problem:

suppose that f and g are functions such that f'(5) = -8 and g'(5) = 0
for h(x) = 4 f(x) - 6g(x) + 6

2007-02-10 06:09:14 · 3 answers · asked by Marla L. 1 in Science & Mathematics Mathematics

3 answers

so what are you supposed to find out?

2007-02-10 06:13:52 · answer #1 · answered by Anonymous · 0 0

Are you supposed to find h'(5)? If so, then take the derivative of the function h(x):

h(x) = 4 * f(x) - 6 * g(x) + 6
h'(x) = 4 * f'(x) - 6 * g'(x)
h'(5) = 4 * f'(5) - 6 * g'(5)
h'(5) = 4 * -8 - 6 * 0
h'(5) = -32

2007-02-10 14:14:42 · answer #2 · answered by Mr. Adkins 4 · 0 0

What's the question here?

2007-02-10 14:15:24 · answer #3 · answered by steiner1745 7 · 0 0

fedest.com, questions and answers